POSITIONING MALAYSIA IN THE REALM OF GLOBAL UNCERTAINTY: ANALYSING ITS CONCERN AND STRUGGLES OF PAKATAN HARAPAN GOVERNMENT (Journal of International Studies, 2020)
The US-China trade war has shackled the political, economic and social landscapes of many nations globally at varying degrees. While trade talks are still ongoing and President Trump has hinted at the possibility of an interim agreement, the prospects of an agreement between the two sides on a comprehensive US-China trade deal in the near-term remains uncertain. Several factors have placed Malaysia to be in a favorable position. One of these factors is that Malaysia continues to be an important geopolitical trading route. In addition to being considered an integral component to the production house of the global supply chain for finished products, Malaysiaâ€™s economy is highly dependent on the movement of goods and global currency. Furthermore, Malaysia is also predominantly reliant on its trades with China. It is suggested that the trade protectionism in the U.S. has resulted into a slowdown of Chinaâ€™s growth, whereby this has created a domino effect on the Malaysian economy. Moreover, the economic prospects of many countries have worsened due to the COVID-19 pandemic, which has led to a shutdown of major operations around the world that has disrupted global supply chains. Countries have employed inward strategies to alleviate national security and domestic economies, at the expense of the globalization process. Although the first wave of the virus has passed and world economies have started to recover, the global economy trajectory is still deemed ambiguous. China, which is a major hub for manufacturing, was heavily affected, and struggles to increase its GDP from 6.1 percent since the end of 2019. Due to the uncertainty on future prospects, the seventh Prime Minister, Dr. Mahathir Mohammed, had established three frameworks that would guide Malaysian foreign policy. Firstly, Malaysia will remain an active participant in all international organizations and treaties that it is a member of. Secondly, Malaysia will communicate its influence towards any decision-making processes in platforms where it is not a member. Thirdly, Malaysia will align its aims to the Industrial Revolution 4.0 and the blue economy. Should this be the way forward from 2020 onwards, or would new strategies need to be crafted? What are the contemporary indicators that Malaysia should consider? Finally, what would be the ultimate message that would be delivered when Malaysia positions itself for its increasing potential in the near future? These questions will help guide this study in its examination of the feasibility of change in Continuity, as a strategy for Malaysian foreign policy in the near future.